2018
DOI: 10.1093/infdis/jiy115
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Prolonged Viral Shedding in Patients With Avian Influenza A(H7N9) Virus Infection

Abstract: Corticosteroid therapy and delayed NAI treatment were associated with prolonged A(H7N9) RNA shedding. NAI combination therapy and double-dose oseltamivir treatment were not associated with a reduced A(H7N9) shedding duration as compared to standard-dose oseltamivir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
83
2
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 40 publications
16
83
2
1
Order By: Relevance
“…In severe influenza virus infection, prolonged viral shedding was associated with fatal outcome and delayed antiviral treatment was an independent risk factor for prolonged virus detection. 36 Similarly, effective antiviral treatment might improve outcomes in COVID-19, although we did not observe shortening of viral shedding duration after lopinavir/ritonavir treatment in the current study. Ran domised clinical trials for lopinavir/ ritonavir (ChiCTR2000029308) and intravenous remdesivir (NCT04257656, NCT04252664) in treatment of COVID-19 are currently in progress.…”
Section: Discussioncontrasting
confidence: 63%
“…In severe influenza virus infection, prolonged viral shedding was associated with fatal outcome and delayed antiviral treatment was an independent risk factor for prolonged virus detection. 36 Similarly, effective antiviral treatment might improve outcomes in COVID-19, although we did not observe shortening of viral shedding duration after lopinavir/ritonavir treatment in the current study. Ran domised clinical trials for lopinavir/ ritonavir (ChiCTR2000029308) and intravenous remdesivir (NCT04257656, NCT04252664) in treatment of COVID-19 are currently in progress.…”
Section: Discussioncontrasting
confidence: 63%
“…Several observational studies have reported that corticosteroid therapy was linked to persistent viral RNA shedding in patients with avian influenza A (H7N9), MERS, and SARS [23][24][25]. Corticosteroid usage was related to prolonged viral RNA shedding time in this report as well, as patients with early RNA clearance had lower proportion of patients using corticosteroid compared with patients with late RNA clearance (40.5% vs 64.5%, P = .025).…”
Section: Discussionsupporting
confidence: 53%
“…Multiple studies have reported that corticosteroid treatment is associated with prolonged influenza viral shedding in hospitalized patients [117][118][119], including in sporadic human infections with avian influenza A(H7N9) virus in China [120], and increased rates of secondary bacterial and fungal co-infections [121,122], which may lead to adverse clinical outcomes. However, there is some evidence to suggest that the increased risk attributed to corticosteroid treatment is a result of bias in observational studies.…”
Section: Treatment Of Influenzamentioning
confidence: 99%